Leukocyte Telomere Length and Polycystic Ovary Syndrome: A Transethnic Mendelian Randomization Study - Lan Cao; Jie Chen (Journal of Bio-X Research)
Objective: Observational studies have reported conflicting results on the association between leukocyte telomere length (LTL) and polycystic ovary syndrome (PCOS). This study evaluated the causal effect of LTL on PCOS in European and East Asian populations using Mendelian randomization (MR). Methods: Genetic variants for LTL were selected as instrumental variables from the largest genome-wide association study (GWAS) from the UK Biobank (472,174 participants) and a Singapore Chinese GWAS (23,096 participants). Two-sample MR analysis was performed in a PCOS cohort of European ancestry (4,138 cases and 20,129 controls), with replication analyses in a Northern European PCOS cohort (3,609 cases and 229,788 controls) and in a Chinese PCOS cohort (4,386 cases and 8,017 controls). A reverse MR study was conducted to test the effect of PCOS on LTL. Results: In the PCOS cohort of European ancestry, genetically determined longer LTL was associated with lower risk of PCOS according to the inverse-variance weighted method [odds ratio (OR), 0.709; 95% confidence interval (CI), 0.506 to 0.992; P = 0.045]. The results remained directionally consistent in sensitivity analyses using different MR methods. In the Northern European replication cohort, a significant association was also found between genetically determined longer LTL and lower risk of PCOS via the MR–Egger method (OR, 0.580; 95% CI, 0.351 to 0.961; P = 0.038). Similar associations were observed in the East Asian replication cohort but did not reach nominal significance. In the reverse MR analysis, no evidence of associations was observed between genetically determined PCOS and LTL in either Europeans or East Asians. Conclusion: This study revealed evidence supporting a causal role of LTL in the etiology of PCOS.